Epidendrum lasiostachyum (Orchidaceae): a new Colombian species of the Epidendrum macrostachyum group - Hágsater, Eric; Santiago Ayala, Elizabeth; Rodríguez-Martínez, Lizeth (Lankesteriana: International Journal on Orchidology, 2016)
In Epidendrum, considered a monophyletic genus, diverse groups can be recognized by their similar vegetative and floral characteristics. The revision of one of these groups, the macrostachyum group, recognized by the monopodial habit, with sub-apical branching, apical, erect inflorescence, non-resupinate, fleshy flowers, and entire lip, embracing the column, pubescent at least at the base, has led to the description of several new species, including a new species from Colombia that is here described and illustrated. The species is similar to Epidendrum microrigidiflorum Hágsater, but differs in the inflorescence (distichous, 6 flowered vs. racemose, 8-16 flowered), the shape (trullate vs. widely rhombic) and ornamentation of the lip (sericeous vs. minutely papillose), and the lack of calli on the disc of the lip (ecallose vs. bicallose). In addition, a key to the 41 species of the group is provided.